PFN1 and integrin‐β1/mTOR axis involvement in cornea differentiation of fibroblast limbal stem cells. Issue 11 (12th September 2019) - Tomasello, Laura; Coppola, Antonina; Pitrone, Maria; Failla, Valentina; Cillino, Salvatore; Pizzolanti, Giuseppe; Giordano, Carla
Abstract: Ex vivo limbal stem cell transplantation is the main therapeutic approach to address a complete and functional re‐epithelialization in corneal blindness, the second most common eye disorder. Although important key points were defined, the molecular mechanisms involved in the epithelial phenotype determination are unclear. Our previous studies have demonstrated the pluripotency and immune‐modulatory of fibroblast limbal stem cells (f‐LSCs), isolated from the corneal limbus. We defined a proteomic profile especially enriched in wound healing and cytoskeleton‐remodelling proteins, including Profilin‐1 (PFN1). In this study we postulate that pfn‐1 knock down promotes epithelial lineage by inhibiting the integrin‐β1(CD29)/mTOR pathway and subsequent NANOG down‐expression. We showed that it is possible modulate pfn1 expression levels by treating f‐LSCs with Resveratrol (RSV), a natural compound: pfn1 decline is accompanied with up‐regulation of the specific differentiation epithelial genes pax6 (paired‐box 6), sox17 (sex determining region Y‐box 17) and ΔNp63‐α (p63 splice variant), consistent with drop‐down of the principle stem gene levels. These results contribute to understand the molecular biology of corneal epithelium development and suggest that pfn1 is a potential molecular target for the treatment of corneal blindness based on epithelial cell dysfunction.